Modeling, Optimization, and Simulation of Nanomaterials-Based Organic Thin Film Transistor for Future Use in pH Sensing - Moorthy, Vijai M.; Mohan, Viranjay Srivastava (Recent Patents on Nanotechnology, 2024)
Introduction: Applications of Organic Thin Film Transistor (OTFT) range from flexible screens to disposable sensors, making them a prominent research issue in recent decades. A very accurate and exact pH sensing determination, including biosensors, is essential for these sensors.Methods: In this present research work, authors have proposed a nanomaterial-based OTFT for future pH monitoring and other biosensing applications. This work presents a numerical model of a pH sensor based on Carbon Nano Tubes (CNTs). Sensing in harsh conditions may be possible with the CNTs due to their strong chemical and thermal resilience. This research work describes the numerical modeling of Bottom-Gate Bottom-Contact (BGBC) OTFTs with a Semiconducting Single-Walled Carbon Nanotube (s-SWCNT) and C60 fullerene blended active layer.Results: The design methodology of organic nanomaterial-based OTFTs has been presented with various parameter extraction precisely its electrical characteristics, modeled by adjusting the parameters of the basic semiconductor technology. For an active layer thickness of 200 nm, the drain current of the highest-performing s-SWCNT:C60 -based OTFT structure was around 4.25 A. This demonstrates that it is better than previously reported patents and published works.Conclusion: This allows for an accurate representation of the device's electrical characteristics. Using Gold (Ag) Source/Drain (S/D) and back-gate electrodes as the medium for sensing, it has been realized how the thickness of the active layer impacts the performance of an OTFT for pH sensor applications.
Keywords: pH sensors